2019
DOI: 10.1080/07853890.2018.1560164
|View full text |Cite
|
Sign up to set email alerts
|

Humanization of nursing care in the emergency service: a systematic review

Abstract: negative influence associated with work, such as stress and burnout. NPE has a positive indirect effect in JS through team/work group cohesion, multidisciplinarity, lack of organizational resources/constraints, working conditions/increased workload, labor discrimination, benefits and rewards, lack of clarity in nurses' responsabilities, patients and doctors' perceptions, poor leadership skills, promotion and professional development opportunities, distributive justice, negative affectivity. Nurses' JS is stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Lotfi(2019) assessed professional nurse-patient communication and showed a correlation between nurse-patient communication and patient satisfaction with nursing care. Rôlo et al(2019) found that receiving adequate nursing care increased patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Lotfi(2019) assessed professional nurse-patient communication and showed a correlation between nurse-patient communication and patient satisfaction with nursing care. Rôlo et al(2019) found that receiving adequate nursing care increased patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%